Manajemen Perencanaan Pembelajaran Aktif di Lembaga ‎Kursus Bahasa Arab Al-Azhar Pare Kediri - Muhammad Kholilur Rosyid; Moch Sulthoni Faizin; Nazahah Ulin Nuha; Zakiyah Arifa (LISANIA: Journal of Arabic Education and Literature, 2019)
Al-Azhar is one of the famous foreign language courses in Pare Kediri. This research is conducted because Al-Azhar Course Institute has interesting programs, and some teaching staff are native Arabs (Yemen), and use fun methods that make it easier for students to understand and Arabic quickly. This study aims to describe the planning and design of learning in Al-Azhar course institutions. This study uses qualitative research with descriptive methods. Data collection is done by observation, interview and documentation. Data is obtained from informants who are instructors at the Al-Azhar Course Institute. Data analysis in this study consists of 3 stages, namely: Data Condensation, Data Display, and Conclusion Drawing / Verification. The results obtained in this study are: First, the planning carried out by the Al-Azhar course institution is a type of project planning, and top-down planning. Second, the design of learning that is carried out is initiated by placement test, then determines the material that is in accordance with students' abilities, and finally evaluates.